Energy management of hybrid electric vehicles based on inverse reinforcement learning - Hengxu Lv; Chunyang Qi; Chuanxue Song; Shixin Song; Ruiqiang Zhang; Feng Xiao (Energy Reports, 2022)
Many scholars have conducted research on reinforcement learning in energy management, and verified that reinforcement learning methods have certain advantages. The guiding direction of the interaction between the agent and environment is determined by the reward function. However, the current design of the reward function still has drawbacks. In most reinforcement learning energy management strategies, the design of the reward function is subjective and empirical, and describing the intention of the expert objectively is difficult. However, this condition cannot guarantee that the agent learns the optimal driving strategy under a given reward function. To address these problems, an energy management strategy based on reverse reinforcement learning is proposed to obtain the reward function weight under the expert trajectory, and then it is used to guide the behavior of the engine agent and the battery agent. Finally, the revised weights are re-entered into the forward reinforcement learning training. From the engine operating point, fuel consumption value, SOC change curve, and reward training process, indicate that the algorithm has certain advantages. In summary, the fuel-saving effect of the proposed algorithm is improved between 5%–10%.